Benefits and challenges of presurgical nasoalveolar molding placement for a unilateral cleft lip and palate a case series: Manfaat dan tantangan pemasangan presurgical nasoalveolar molding pada celah bibir lelangit unilateral serangkaian kasus - Nurahma, Rifaat; Rahmah, Nur; Permatasari, Andi Sri; Sudarman, Ian Afifah; Alwi, Ita Purnama (Makassar Dental Journal, 2025)
Pre-surgical nasoalveolar moulding (PNAM) has been applied to reshape the divided nasal structure, facilitate surgical interven-tion, and reduce the severity and tension of the cleft. This article presents three cases of patients with unilateral cleft lip and pa-late (UCLP) who underwent PNAM prior to surgery, highlighting the diverse cases of cleft and patient characteristics, which aid in the management of nasal clefts and yield more robust evidence-based outcomes. The main challenge in PNAM therapy is en-suring patient and family caregiver compliance with treatment, given that young patients must adapt to the device fitting and activation. Monitoring also requires regular and repeated visits, which can be time-consuming and cause psychological stress due to witnessing the patient's adaptation to the device. It is concluded that PNAM treatment reduces the width of the alveolar cleft. This treatment improves nasal symmetry by altering the columella angle, maintaining alar width, extending the height of the nos-trils on the affected side, and increasing columella length. Cooperation between patients, family caregivers, and the medical team is essential for better outcomes.